Circulating biomarkers for management of cancer therapeutics-related cardiac dysfunction. Issue 3 (31st May 2022) - Tonry, Claire; Russell-Hallinan, Adam; McCune, Claire; Collier, Patrick; Harbinson, Mark; Dixon, Lana; Watson, Chris J
Abstract: Cancer therapeutics-related cardiac dysfunction (CTRCD) has emerged as a major cause of morbidity and mortality in cancer survivors. Effective clinical management of CTRCD is impeded by a lack of sensitive diagnostic and prognostic strategies. Circulating molecular markers could potentially address this need as they are often indicative of cardiac stress before cardiac damage can be detected clinically. A growing understanding of the underlying physiological mechanisms for CTRCD has inspired research efforts to identify novel pathophysiologically relevant biomarkers that may also guide development of cardio-protective therapeutic approaches. The purpose of this review is to evaluate current circulating biomarkers of cardiac stress and their potential role in diagnosis and management of CTRCD. We also discuss some emerging avenues for CTRCD-focused biomarker investigations. Graphical Abstract: Graphical abstract Circulating biomarkers for chemotherapeutics-related cardiac dysfunction. Examples of chemotherapeutic reagents that affect cardiac function are shown ( A ). Chemotherapeutic reagents exert toxic effects on the heart via various mechanisms ( B ). Novel technologies are being utilized to investigate biologically relevant markers of cardiac dysfunction in the circulation ( C ).